2021
DOI: 10.1136/bmj.n166
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening capacities and resource allocation for co-production of health research in low and middle income countries

Abstract: and colleagues share experiences and ideas to strengthen capacity for health research co-production in low and middle income countries on 21 February 2021 by guest. Protected by copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, contemporary knowledge systems on power are dominated by Western authors and modes of thinking, 31 32 evidenced by a recent study found that most co-production of health research has been conducted in highly developed settings, with less than 2% of co-production literature examining low- and middle-income countries (LMICs). 2 Engaging with perspectives of participatory health researchers—particularly those from the Global South—and considering how experiences vary across countries, disciplines and income contexts, will help to produce more nuanced understandings of power in real-world settings, providing a platform for voices that are often missing from the research scholarship on power. The qualitative data generated from exploration of these perspectives can be used to develop concrete actions to address power inequities in PHR partnerships, and to validate the ‘Social Ecology of Power’ framework described above, which at present draws only from peer reviewed literature and the experiential knowledge of it's author.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, contemporary knowledge systems on power are dominated by Western authors and modes of thinking, 31 32 evidenced by a recent study found that most co-production of health research has been conducted in highly developed settings, with less than 2% of co-production literature examining low- and middle-income countries (LMICs). 2 Engaging with perspectives of participatory health researchers—particularly those from the Global South—and considering how experiences vary across countries, disciplines and income contexts, will help to produce more nuanced understandings of power in real-world settings, providing a platform for voices that are often missing from the research scholarship on power. The qualitative data generated from exploration of these perspectives can be used to develop concrete actions to address power inequities in PHR partnerships, and to validate the ‘Social Ecology of Power’ framework described above, which at present draws only from peer reviewed literature and the experiential knowledge of it's author.…”
Section: Introductionmentioning
confidence: 99%
“…Several PEA approaches that are participatory in nature could be considered and, when possible, adopted. Despite the fact that these methods still require more theoretical and practical conceptualization, such approaches do follow the principles of coproduction in research [ 48 51 ]. In addition to these general principles, examples of specific methods, borrowed from other disciplines (such as system thinking and social sciences), that are participatory in nature and that can be perfectly suitable for conducting and complementing PEA research include participatory stakeholder mapping jointly conducted with stakeholders [ 52 ], participatory power mapping [ 53 ], group model-building [ 54 ], and mixed-methods approaches to social network analysis [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This near real-time aspect of embedded IR is recognized as one of the advantages as research results can be available within planning cycles for decision making and program adaptation. While the research projects themselves generally require limited funding, building local capacity to run the studies, both for the implementers and local researchers, often requires additional resources beyond the actual research costs for training and technical assistance during the studies, consistent with building capacity of research co-production as discussed by Agyebong and colleagues [ 8 ].…”
Section: Embedded Implementation Research At Unicef: Experiences 2015–2019mentioning
confidence: 99%
“…This paradox demonstrates the urgent need to focus on implementation research (IR) to identify barriers and effective strategies to implementation of existing proven interventions. Evidence of the effect of long-term consistent investments in embedded IR on improved service coverage and efficient use of routine health system resources has recently emerged from Ghana [ 7 , 8 ] and Latin America and the Caribbean [ 9 ].…”
Section: Introduction: Need For Actionable Knowledge To Improve Programs For Childrenmentioning
confidence: 99%